Human diseases and conditions (supplement 2) infectious diseases - Izenberg, Neil (Scribner/Thomson/Gale, 2000)
Presents articles dealing with all kinds of diseases and disorders, from acne and brain tumor to tobacco-related diseases and yellow fever.